Effects of Employee Sickness Presence on Customer Repurchase and Recommendation Intentions: The Role of Customer Affective Reactions - Carolin Dietz; Hannes Zacher (Journal of Business and Psychology, 2021)
Sickness presence can have important individual and organizational consequences, such as health deterioration or productivity loss. Additional risks, such as negative customer reactions, may be particularly relevant in the service sector. Based on affective events theory and appraisal theories, we hypothesize that employee sickness presence negatively impacts customer repurchase and recommendation intentions. Furthermore, we explore potential affective mechanisms of these effects, including disease avoidance, personal anger, moral outrage, post-consumption guilt, and customer compassion for the employee. We conducted four studies, including three experimental vignette methodology studies (Ns0.167em=0.167em227, 72, and 763) and a qualitative study (N0.167em=0.167em54). In Study 1, employee sickness presence had negative effects on repurchase and recommendation intentions. Results of Study 2 show that customers experienced disgust, fear, anger, guilt, compassion, and indifference in response to sickness presence. In Study 3, anger explained the negative effects of employee sickness presence on repurchase and recommendation intentions, while appraisals of moral fairness were negatively related to both customer intentions. Finally, in Study 4, disgust and anger explained negative effects, while fear, guilt, and compassion explained positive effects of employee sickness presence on customer intentions. Appraisals of goal incongruence, reduced agency of the customer, and uncertainty were negatively related to customer intentions. The physical absence of the customer in the service encounter (phone call) mitigated the experience of disgust, fear, and anger, whereas it exacerbated feelings of compassion for the ill employee.
Keywords: 650; Sickness presence; Presenteeism; Customer service